Torquewhirl - A theory to explain nonsynchronous whirling failures of rotors with high load torque - Vance, John (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Numerous unexplained failures of rotating machinery by nosynchronous shaft whirling point to a possible driving mechanism or source of energy not identified by previously existing theory. A majority of these failures have been in machines characterized by overhung disks (or disks located close to one end of a bearing span) and/or high horse power and load torque. This paper gives exact solutions to the nonlinear differential equations of motion for a rotor having both of these characteristics, and shows that high ratios of driving torque to damping can produce nonsynchronous whirling with destructively large amplitudes. Solutions are given for two cases: (1) viscous load torque and damping, and (2) load torque and damping proportional to the second power of velocity (aerodynamic case). Linearized coefficients for stability analyses are derived for a special case. Criteria are given for avoiding the torquewhirl condition.